2018
DOI: 10.3390/s19010108
|View full text |Cite
|
Sign up to set email alerts
|

General Architecture for Development of Virtual Coaches for Healthy Habits Monitoring and Encouragement

Abstract: Good health is the result of a healthy lifestyle, where caring about physical activity and nutrition are key concerns. However, in today’s society, nutritional disorders are becoming increasingly frequent, affecting children, adults, and elderly people, mainly due to limited nutrition knowledge and the lack of a healthy lifestyle. A commonly adopted therapy to these imbalances is to monitor physical activity and daily habits, such as recording exercise or creating custom meal plans to count the amount of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…For future work we plan to evaluate the proposed architecture and services in terms of reliability, availability, conceptual integrity and other key aspects identified in previous work. In particular, the kind of architecture evaluation that we plan carry out will follow standard practice in this kind of research ( [43,44,45] and based on [46] guidelines, including questionnaires and animated multimedia of software architecture models to be evaluated by world-wide experts on systems and software architectures and experienced developers. The huge challenge of combining multiple, possible conflicting or contradictory, sources of information (wearable body sensors, computer vision, nutritional databases, smart devices, frequency food diaries, etc.…”
Section: Discussionmentioning
confidence: 99%
“…For future work we plan to evaluate the proposed architecture and services in terms of reliability, availability, conceptual integrity and other key aspects identified in previous work. In particular, the kind of architecture evaluation that we plan carry out will follow standard practice in this kind of research ( [43,44,45] and based on [46] guidelines, including questionnaires and animated multimedia of software architecture models to be evaluated by world-wide experts on systems and software architectures and experienced developers. The huge challenge of combining multiple, possible conflicting or contradictory, sources of information (wearable body sensors, computer vision, nutritional databases, smart devices, frequency food diaries, etc.…”
Section: Discussionmentioning
confidence: 99%
“…eCoaching has other possibilities when compared to traditional coaching in terms of value addition, performance, and competence. Efficacy [52] study is a problem in both kinds of coaching to date, as revealed in the systematic literature review, for the following reasons: insufficient planning in study selection and study design [1,23], lack of conceptual/contextual clarity [24,25], inappropriate selection of sample size for statistical analysis [61], dearth of proper background education [74], lack of reliance and self-disclosure [1,22], absence of variation in a selected population [22,61], and lack of competence and experience with technology (digital illiteracy) [22,75].…”
Section: Rq5: How Can Ecoaching Promote a Healthy Lifestyle With Proven Coaching Methods Using Ict?mentioning
confidence: 99%
“…A virtual eCoaching recommendation system can guide people and convey the appropriate recommendations in real time to improve their lifestyle [21,22,56]. The leading methods of eCoaching processes are monitoring, decision making, goal setting, persuasion, awareness provision (intervention), goal evaluation, and learning for future actions [24,27,[32][33][34][57][58][59]. Digital techniques of lifestyle change with eCoaching have appeared as efficient and scalable options for intensive behavioral counseling when face-to-face or in-person programs are inaccessible or undesirable.…”
Section: Overviewmentioning
confidence: 99%
“…Current applications of these systems in this domain include conducting interviews [8], providing medical advice [9], helping patients with chronic diseases or recovering at home [10,11], serving as a reminder in medication and prescribed treatments [12,13], advise how to perform exercises or activities aimed at recovery and also ask questions that allow to assess the patient's situation [14,15], detecting potential diseases and illness in patients, and promoting healthy habits such as regular exercise, eating a healthy diet or using sunscreen [16,17,18].…”
Section: Conversational Agents and Robotsmentioning
confidence: 99%